Spectrum of neurosurgical operative interventions at the regional centre for neurosurgery UDUTH Sokoto: a 5 years review - Lasseini, Ali; Koko, Aliyu M.; Isa, Ashafa B.; Ladan, Aliyu; Ladan, Hali; Abdullateef, Abdulhakeem (International Surgery Journal, 2023)
Background: Neurosurgical operative interventions are aimed for the diagnosis and treatment of diseases of the central and peripheral nervous systems. The spectrum of these interventions ranges from cranial, spinal and peripheral interventions, and could also be elective or emergency based on the urgency of the intervention. Data on the spectrum of neurosurgical operative interventions are limited in our environment. The aim of the study is to describe the epidemiological profile, diagnoses and pattern of neurosurgical operative interventions at our center. Methods: This is a retrospective study analyzing the demographic profile, clinical diagnoses and operative interventions of neurosurgical patients managed at our center over a period of 5 years, from January 2014 to December 2018. Results: A total of 784 patients had operative interventions during the study period. Five hundred and twenty (520) patients were males representing 66.3%; paediatric patients accounted for 487 patients (62.1%). Majority of the patients (518 patients: 66.1%) had elective interventions. The commonest indication for neurosurgical intervention during the study period was Neurotrauma (235 patients: 30%), followed by hydrocephalus (218 patients: 27.8%) and then neurooncology (137 patients: 17.5%). Ventriculoperitoneal shunt (218 patients: 27.8%), excision and repair of myelomeningocoele (107 patients: 13.6%) and debridement/elevation for open head injury/ elevation of depressed skull fracture (85 patients: 10.8%) were the commonest operative interventions during study period. Conclusions: Although Ventriculoperitoneal shunt and excision and repair of myelomeningocoele were the commonest operative neurosurgical intervention during the study period, neurotrauma cases constituted the commonest indications for operative surgical intervention.